Development of a smart oval ball for assessment of angular flight dynamics and precision of kick execution - Fuss, F. K.; Smith, R. M. (Sports Technology, 2011)
A smart inflatable oval ball was developed consisting of two simultaneously inflated bladders between which the sensor enclosure was placed, containing three orthogonal MEMS gyroscopes, a data logger and a battery. The smart ball measures the three components of its angular velocity and delivers the following parameters: the spin rate, the precession rate, the spin decay, the position of the spin axis and its elevation angle with respect to the body coordinate system, an index for assessment of kick precision and the wobble angle of the ball with respect to the space coordinate system. The spin-axis vector diagram, colour-coded with progressing time, was displayed on a 3D model of the ball in AutoCAD.